Ethnic, Familial, and Religious Identity of Roma Adolescents in Bulgaria, Czech Republic, Kosovo, and Romania in Relation to Their Level of Well‐Being. Issue 3 (20th March 2017) - Dimitrova, Radosveta; van de Vijver, Fons J. R.; Taušová, Jitka; Chasiotis, Athanasios; Bender, Michael; Buzea, Carmen; Uka, Fitim; Tair, Ergyul
Abstract : This study examines ethnic, national, familial, and religious identity and well‐being of 632 Roma minority and 589 majority adolescents (age: M  =   15.98 years, SD  =   1.34) in Bulgaria, the Czech Republic, Kosovo, and Romania. Results indicated that Roma showed lower endorsement of national identity but stronger religious identity than their majority counterparts. Path models showed positive associations of familial and religious identities with well‐being, whereas Roma identity was negatively associated with well‐being, particularly for Roma in Bulgaria and Kosovo (countries with a less active policy toward improving conditions of Roma). In the latter countries, Roma ethnic identity is less relevant and weakly associated with psychological well‐being of youth. Abstract : The title for this Special Section isContext and Ethnic/Racial Identity, edited by Eleanor K. Seaton, Stephen Quintana, Maykel Verkuyten, and Gilbert C. Gee